Behavioral adaptation of sympatric rodents to early germination of oak acorns: radicle pruning and embryo excision - Zhang, Mingming; Yang, Xifu; Dong, Zhong; Liu, Shuyuan; Chen, Huanhuan; Yi, Xianfeng (Frontiers in Plant Science, 2023)
The seed germination schedule is a key factor affecting food-hoarding behaviour and seedling regeneration. However, little is known about the behavioural adaptation of rodents to the rapid germination of acorns. In this study, we provided acorns of Quercus variabilis to several rodent species to explore how food-hoarding animals respond to seed germination. All rodent species preferred to prune radicles of germinating acorns before caching, indicating that radicle pruning was a stable and more general foraging behaviour strategy for food-hoarding rodents. Moreover, rodents with stronger scatter-hoarding abilities preferred to scatter-hoard and prune more germinating acorns, whereas consumed more non-germinating acorns. We reported the first evidence of embryo excision of Apodemus peninsulae, representing an early stage in the evolutionary response to seed perishability. Acorns with embryo excised rather than with radicle pruned were far less likely to germinate than the intact acorns, suggesting the behavioural adaptation strategy of rodents to rapid germination of recalcitrant seeds. This study provides insights into the impact of early seed germination on plant-animal interactions.